Spatially Confined Spin Polarization and magnetic sublattice control in (La,Sr)MnO3−δ Thin Films by Oxygen Vacancy Ordering - Magnus Moreau (Nature Portfolio, 2017)
Abstract Perovskite oxides are known for their strong structure property coupling and functional properties such as ferromagntism, ferroelectricity and high temperature superconductivity. While the effect of ordered cation vacancies on functional properties have been much studied, the possibility of tuning the functionality through anion vacancy ordering has received much less attention. Oxygen vacancies in ferromagnetic La0.7Sr0.3MnO3−δ thin films have recently been shown to accumulate close to interfaces and form a brownmillerite structure (ABO2.5). This structure has alternating oxygen octahedral and tetrahedral layers along the stacking direction, making it a basis for a family of ordered anion defect controlled materials. We use density functional theory to study how structure and properties depend on oxygen stoichiometry, relying on a block-by-block approach by including additional octahedral layers in-between each tetrahedral layer. It is found that the magnetic and electronic structures follow the layers enforced by the ordered oxygen vacancies. This results in spatially confined electronic conduction in the octahedral layers, and decoupling of the magnetic sub-lattices in the octahedral and tetrahedral layers. These results demonstrate that anion defect engineering is a promising tool to tune the properties of functional oxides, adding a new avenue for developing functional oxide device technology.